PELATIHAN ANALISIS REGRESI LINIER BERGANDA DENGAN APLIKASI JASP BAGI MAHASISWA STIE PEMBANGUNAN TANJUNGPINANG KEPULAUAN RIAU - Sofyan, Mohammad; Marlinda, Charly; Satriadi, Satriadi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The preparation of scientific papers for final year students is still constrained in terms of data processing using statistics, thus submitting it to other parties. Therefore, assistance and training are needed using an application, one of which is JASP to analyze multiple linear regression. The obstacle faced by students so far is analyzing data with statistics. This method of community service by training and mentoring students at STIE Pembangunan Tanjungpinang Kepulauan Riau in completing the final project, 100 students participated. The results of this training show that it is useful to complete the task. In the future, there should be more practice in class so that students don’t forget when doing research